6x(6x-5)-3(5-6x)=

Simple and best practice solution for 6x(6x-5)-3(5-6x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x(6x-5)-3(5-6x)= equation:


Simplifying
6x(6x + -5) + -3(5 + -6x) = 0

Reorder the terms:
6x(-5 + 6x) + -3(5 + -6x) = 0
(-5 * 6x + 6x * 6x) + -3(5 + -6x) = 0
(-30x + 36x2) + -3(5 + -6x) = 0
-30x + 36x2 + (5 * -3 + -6x * -3) = 0
-30x + 36x2 + (-15 + 18x) = 0

Reorder the terms:
-15 + -30x + 18x + 36x2 = 0

Combine like terms: -30x + 18x = -12x
-15 + -12x + 36x2 = 0

Solving
-15 + -12x + 36x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(-5 + -4x + 12x2) = 0

Factor a trinomial.
3((-1 + -2x)(5 + -6x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5

Subproblem 2

Set the factor '(5 + -6x)' equal to zero and attempt to solve: Simplifying 5 + -6x = 0 Solving 5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 0 + -5 -6x = 0 + -5 Combine like terms: 0 + -5 = -5 -6x = -5 Divide each side by '-6'. x = 0.8333333333 Simplifying x = 0.8333333333

Solution

x = {-0.5, 0.8333333333}

See similar equations:

| x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 | | 6+ln(x+5)=8 | | Xsquared+5cubed=9cubed | | 9x^4-16=10x^2-17 | | 8x-18=36-6x | | 3*(15-x)=18 | | 2(3x-1)=4 | | 3*(x-15)=18 | | 5(7m-3)=14(2m+5) | | 3*(x-15)=48 | | V=6(8x+2)(5x-4)-10(5x-4) | | (2y-1)dy=(3x^2+1)dx | | 4x=190 | | (2y-1)dy=(3x+1)dx | | 2ln(5x+1)=14 | | 12a-11=15a-10 | | 10z+4=1 | | 3(x+4)-12x=48 | | lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 | | 12x-11=15x-10 | | 12=(n-1)(n-2)(n-3)(n-4)(n-5)-3n^2 | | -36=y-5y-21 | | 12=(n-1)(n-2)(n-3)(n-4)-(2n^3) | | 12=n^4-12n^3+35n^2-50n+24 | | 8+4x=7x | | -11-5X=-111 | | (y+3)2=25 | | 8x=20x^2 |

Equations solver categories